The Election Commission of India and the Regulation and Administration of Electoral Politics: A Review - Kareppa Bagappa B. Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Since India’s independence, the Election Commission has been central to the administration and regulation of electoral politics. Over time, especially since the 1990s, its scope and authority have expanded significantly. This article employs multiple case studies to examine the Commission’s regulatory developments in contemporary Indian politics. It explores efforts to oversee the timing, conduct, and reporting of elections, alongside initiatives to regulate voter, candidate, and party engagement. The paper evaluates the impact of these legislative measures on electoral practices in India. Despite the political implications of its decisions, the Election Commission has maintained a reputation for independence, enabling it to intervene effectively in electoral administration. The study aims to assess the Commission’s effectiveness, organizational structure, and its role in extending constitutional provisions, ultimately highlighting its function as a politically neutral body that safeguards democratic processes.